Anthropogenic influences on riverine fluxes of dissolved inorganic carbon to the oceans - Raymond, Peter A.; Hamilton, Stephen K. (Limnology and oceanography letters, 2018)
Bicarbonate (HCO3−), the predominant form of dissolved inorganic carbon in natural waters, originates mostly from watershed mineral weathering. On time scales of decades to centuries, riverine fluxes of HCO3− to the oceans and subsequent reactions affect atmospheric CO2, global climate and ocean pH. This review summarizes controls on the production of HCO3− from chemical weathering and its transport into river systems. The availability of minerals and weathering agents (carbonic, sulfuric, and nitric acids) in the weathering zone interact to control HCO3− production, and water throughput controls HCO3− transport into rivers. Human influences on HCO3− fluxes include climate warming, acid precipitation, mining, concrete use, and agricultural fertilization and liming. We currently cannot evaluate the net result of human influences on a global scale but HCO3− fluxes are clearly increasing in some major rivers as shown here for much of the United States. This increase could be partly a return to pre‐industrial HCO3− fluxes as anthropogenic acidification has been mitigated in the United States, but elsewhere around the world anthropogenic acidification could be leading to decreased concentrations and fluxes.